Direct Double Coating of Carbon and Nitrogen on Fluoride-Doped Li4Ti5O12 as an Anode for Lithium-Ion Batteries - Lukman Noerochim; Alvalo Toto Wibowo; Widyastuti; Achmad Subhan; Bambang Prihandoko; Wahyu Caesarendra (Batteries, 2022)
Graphite as a commercial anode for lithium-ion batteries has significant safety concerns owing to lithium dendrite growth at low operating voltages. Li4Ti5O12 is a potential candidate to replace graphite as the next-generation anode of lithium-ion batteries. In this work, fluoride-doped Li4Ti5O12 was successfully synthesized with a direct double coating of carbon and nitrogen using a solid-state method followed by the pyrolysis process of polyaniline. X-ray diffraction (XRD) results show that the addition of fluoride is successfully doped to the spinel-type structure of Li4Ti5O12 without any impurities being detected. The carbon and nitrogen coating are distributed on the surface of Li4Ti5O12 particles, as shown in the Scanning Electron Microscopy–Energy Dispersive X-ray Spectroscopy (SEM-EDS) image. The Transmission Electron Microscopy (TEM) image shows a thin layer of carbon coating on the Li4Ti5O12 surface. The fluoride-doped Li4Ti5O12 has the highest specific discharge capacity of 165.38 mAh g−1 at 0.5 C and capacity fading of 93.51% after 150 cycles compared to other samples, indicating improved electrochemical performance. This is attributed to the synergy between the appropriate amount of carbon and nitrogen coating, which induced a high mobility of electrons and larger crystallite size due to the insertion of fluoride to the spinel-type structure of Li4Ti5O12, enhancing lithium-ion transfer during the insertion/extraction process.